'Just like studying abroad': an analysis of the online promotional videos of Thai university international programmes. Issue 2 (2nd July 2020) - Kraus, Harald; Burford, James
ABSTRACT: Universities around the world increasingly use online videos to recruit both domestic and international students. However, little is currently known about how such videos are used to market international programmes in the Global South. We analysed a sample of 19 videos that promote international programmes at Thai universities. After transcribing the videos, we conducted a thematic analysis of their overall features. We found that, despite some attempts to address international students, the primary audience that was targeted was domestic. Our analysis revealed that the videos constructed international higher education (IHE) as offering: intercultural experiences with regard to learning, languages, careers and exchange, and the opportunity to have an international experience with the comforts of home. The videos also tended to position IHE as advancing the development of the host nation. Based on our analysis, we argue that further nuanced thinking regarding the meaning and promotion of IHE in Thailand is required.